Spuriously Elevated Serum IGF-1 in Adult Individuals with Delayed Puberty: A Diagnostic Pitfall. (15th August 2010) - Imran, Syed Ali; Pelkey, Michael; Clarke, David B.; Clayton, Dale; Trainer, Peter; Ezzat, Shereen
Abstract : Serum insulin-like growth factor-1 (IGF-1) is a sensitive marker of growth hormone (GH) activity. The levels of IGF-1 vary widely, peaking during puberty and declining with advancing age. During adolescence, serum IGF-1 levels tend to correlate better with pubertal stage rather than chronological age. Here we discuss two cases of delayed puberty, both in their 20s, who presented with high serum IGF-1 but no clinical or biochemical evidence of hypersomatotropism as confirmed by appropriate GH response to an oral glucose challenge. Both individuals achieved full pubertal status with testosterone replacement therapy and their serum IGF-1 levels settled into normal age-specific range. We suggest that in chronologically adult individuals with delayed puberty, serum IGF-1 should not be interpreted on the basis of age-specific normal values but rather on their pubertal status. Furthermore, in the absence of another cause of elevated IGF-1, the expectation is that IGF-1 levels will decline towards age-normative ranges following androgen replacement therapy.